2000
DOI: 10.1021/jf000368f
|View full text |Cite
|
Sign up to set email alerts
|

Foliar Application of Selenite and Selenate to Potato (Solanumtuberosum): Effect of a Ligand Agent on Selenium Content of Tubers

Abstract: The effect of a foliar spray of selenium on potatoes was investigated for 2 years. Amounts of 0, 50, and 150 g of Se ha(-)(1) were applied both as sodium selenate and as sodium selenite in water, either pure or with the addition of 0.15% of soluble leonardite as a source of humic acids (pH 7). Tuber selenium concentration increased with the application levels, both with sodium selenate and with sodium selenite, when only aqueous solutions were used. When humic acids were added, the tuber selenium level rose mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(63 citation statements)
references
References 12 publications
4
58
0
1
Order By: Relevance
“…Boldrin et al (2013) indicated that, soil application of Se gave higher content of P compared with foliar application on rice. Similar results were also reported by Hu et al (2002) on rice and Poggi et al ( 2000) on potato.…”
Section: Percentages Of Potassium:results Shown Insupporting
confidence: 91%
“…Boldrin et al (2013) indicated that, soil application of Se gave higher content of P compared with foliar application on rice. Similar results were also reported by Hu et al (2002) on rice and Poggi et al ( 2000) on potato.…”
Section: Percentages Of Potassium:results Shown Insupporting
confidence: 91%
“…Sin embargo, la fortificación agronómica de las plantas cultivadas mediante aplicación foliar con Se es aún poco usada (kÁPOLNA et al, 2009). A pesar de ello, la pulverización foliar de Se(IV) o Se(VI) para aumentar el contenido de Se se ha realizado con éxito en muchos cultivos, como la patata (POGGI et al, 2000), arroz (HU et al, 2002), soja (YANG et al, 2003, col, cebolla, ajo y rábano (SLEJKOVEC y GOESSLER, 2005), trigo y calabaza (SMRKOLJ et al, 2005;SMRKOLJ et al, 2006). No obstante, en el caso de la fresa (Fragaria x ananassa Duch.…”
Section: P Palencia Et Al Introducciónunclassified
“…Meat and fish are rich source of selenium, mostly in Se-cys form. On the other hand, vegetable and fruit are lower-grade source of selenium, occurring mostly in more acceptable form -Se-met [11]. Surai [3] presents the following acceptability of Se forms: Semet > SeO4 2-> SeO3 2-.…”
Section: Sources and Forms Of Selenium In Human Nutritionmentioning
confidence: 99%
“…Figure 5. Increase of concentration of selenium in potato tubers after foliar application [11] Selenium is not considered essential nutrient of vascular plants although in case of its deficiency the reduction of rice (Oriza sativa L.) and wheat (Triticum eastivum L.) growth, higher sensibility of Perennial Ryegrass (Lolium perenneL.) and lettuce (Lactuca sativa L.) to UV radiation [8] were observed.…”
Section: Selenium In Plantsmentioning
confidence: 99%
See 1 more Smart Citation